2019
DOI: 10.1016/j.engstruct.2019.109815
|View full text |Cite
|
Sign up to set email alerts
|

Influence of traditional earthquake-resistant techniques on the out-of-plane behaviour of stone masonry walls: Experimental and numerical assessment

Abstract: Influence of traditional earthquake-resistant techniques on the out-of-plane behavior of stone masonry walls: experimental and numerical assessment. Engineering Structures (2020).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 22 publications
1
8
0
Order By: Relevance
“…They allow estimating masonry elastic properties because of the relationship between the sonic wave velocity propagating through the material and its elastic mechanical properties (Everett 2013). The validity of the test has been widely demonstrated through onsite and laboratory works (Miranda et al 2012;Miranda et al 2016;Maccarini et al 2019;Murano et al 2019;Sánchez-Aparicio et al 2019). Even if specific standards to follow for sonic tests on masonry structures do not exist, the procedure is based on the same physical principles as the ultrasonic pulse velocity method developed for testing concrete, which adopts a procedure well-established by international standards (ASTM C597-09 2009; CEN12504-04 2004).…”
Section: Sonic Tests Are Indisputably the Most Applied Non-destructiv...mentioning
confidence: 99%
“…They allow estimating masonry elastic properties because of the relationship between the sonic wave velocity propagating through the material and its elastic mechanical properties (Everett 2013). The validity of the test has been widely demonstrated through onsite and laboratory works (Miranda et al 2012;Miranda et al 2016;Maccarini et al 2019;Murano et al 2019;Sánchez-Aparicio et al 2019). Even if specific standards to follow for sonic tests on masonry structures do not exist, the procedure is based on the same physical principles as the ultrasonic pulse velocity method developed for testing concrete, which adopts a procedure well-established by international standards (ASTM C597-09 2009; CEN12504-04 2004).…”
Section: Sonic Tests Are Indisputably the Most Applied Non-destructiv...mentioning
confidence: 99%
“…Figures 16 and 17 show the variation of equivalent viscous damping and cumulative energy dissipated for different displacement levels, and Table 4 shows the variation of cumulative energy of specimens after the test. The equivalent viscous damping (βeq) was estimated as per the recommendations of ATC [31] and Hou et al [32], as given in Equations ( 1) and (2).…”
Section: Energy Dissipation and Equivalent Viscous Dampingmentioning
confidence: 99%
“…Different from other traditional masonry structures, the strength of the stone is far higher than that of the filling material in mortar joints. By combining experimental and analytical approaches, as well as field investigations of earthquake damage to stone structures, it has been found that the mortar joint of a stone wall is the weakest zone under earthquake [1,2]. Despite past literature having developed different strengthening options of stone masonry joints [3][4][5][6][7][8], the seismic behavior has not yet been assessed.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…From an experimental standpoint, several works investigating tests aimed at understanding the load-bearing capacity of masonry vaults or structures in-and out-of-plane loaded through the application of incremental horizontal and vertical loads have been proposed in the technical literature [32][33][34][35][36][37]. In other papers [38][39][40][41], the dynamic response of masonry is inspected by means of tests carried out on shaking tables using in-scale models.…”
Section: Introductionmentioning
confidence: 99%